2017
DOI: 10.1021/acs.est.6b06210
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberrations in Large Japanese Field Mice (Apodemus speciosus) Captured near Fukushima Dai-ichi Nuclear Power Plant

Abstract: Since the Fukushima Dai-ichi Nuclear Power Plant accident, radiation effects on nonhuman biota in the contaminated areas have been a major concern. Here, we analyzed the frequencies of chromosomal aberrations (translocations and dicentrics) in the splenic lymphocytes of large Japanese field mice (Apodemus speciosus) inhabiting Fukushima Prefecture. A. speciosus chromosomes 1, 2, and 5 were flow-sorted in order to develop A. speciosus chromosome-specific painting probes, and FISH (fluorescence in situ hybridiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Thus, various indexes should be applied to evaluate the exposure effects on the species. In fact, chromosomal aberrations in the splenic lymphocytes of field mice captured near FNPP were reported [20]. Frequencies of translocations and dicentrics per cell (%) of the field mice distribution in "the heavily contaminated area (ambient dose equivalent rate = 80.0 μSv/h)" were significantly higher than that of the control area (ambient dose rate was 0.1 μSv/h), slightly contaminated area (ambient dose equivalent rate ranging from 0.3 to 0.4 μSv/h), and moderately contaminated area (ambient dose equivalent rate ranging from 7.5 to 30.7 μSv/h).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, various indexes should be applied to evaluate the exposure effects on the species. In fact, chromosomal aberrations in the splenic lymphocytes of field mice captured near FNPP were reported [20]. Frequencies of translocations and dicentrics per cell (%) of the field mice distribution in "the heavily contaminated area (ambient dose equivalent rate = 80.0 μSv/h)" were significantly higher than that of the control area (ambient dose rate was 0.1 μSv/h), slightly contaminated area (ambient dose equivalent rate ranging from 0.3 to 0.4 μSv/h), and moderately contaminated area (ambient dose equivalent rate ranging from 7.5 to 30.7 μSv/h).…”
Section: Discussionmentioning
confidence: 99%
“…Fukumoto and colleagues have recently reported changes in gene expression in the small intestine of pigs 34 , DNA damage in bovine lymphocytes 35 , and enhanced spermatogenesis in large Japanese field mice 36 . Another independent group has also reported chromosomal aberrations in large Japanese field mice 37 . In contrast, some studies have reported no detectable effects.…”
Section: Introductionmentioning
confidence: 98%
“…Okano et al [17] reported that, although the concentrations of 134 Cs and 137 Cs in wild mice from Fukushima exceeded 4000 Bq/kg, there were no significant differences in the frequencies of apoptotic cells or morphologically abnormal sperm when compared with wild mice from the non-contaminated control area. However, Kawagoshi et al [18] reported that the average frequencies of chromosomal aberrations in splenic lymphocytes of animals living in the heavily contaminated (approximately 3 mGy/day) area of Fukushima were higher than those of animals from the non-contaminated, slightly contaminated (approximately 0.03 mGy/day), and moderately contaminated (approximately 1 mGy/day) areas. Moreover, the aberration frequency in individual wild mice tended to increase with the estimated dose rates and accumulated doses.…”
Section: Resultsmentioning
confidence: 99%